HUBUNGAN TINGKAT PENDIDIKAN, TEMPAT TINGGAL DAN INFORMASIPETUGAS LAPANGAN KELUARGA BERENCANA (PLKB) TERHADAP UNMET NEED KB PADA WANITA KAWIN - Hanum Kholida Zia (The Indonesian Journal of Public Health, 2019)
Family Planning Program has some indicators of success; one of the indicators is unmet needs of family planning services. The success of the unmet need indicator services is the decrease of unmet need to 9.9% in 2019. In 2012, the number of unmet need for family planning amounted to 11.4%. This study aims to identify whether there is a correlation of the education level, residence, and information of family planning field officers with unmet needs for family planning in East Java. This research was conducted with a cross-sectional design with the data from the 2012 Indonesian Demographic and Health Survey. There is a correlation of the education level (p=0.000), residence (p=0.010), and information of family planning field officer (p = 0.048) with the unmet needs for family planning. The research cocludes that education level, residence, and information from health centre affect the unmet need for family planning.